THE INFLUENCE OF AUDIT TENURE, COMPANY SIZE, AUDIT ROTATION, AND PROFITABILITY ON GOING CONCERN AUDIT OPINION IN REAL ESTATE AND PROPERTY SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2021-2024 - Winnie Trecia; Hottua Samosir; Audris Lrticia; Felicia; Margaretha; Elfina Okto Posmaida Damanik (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The purpose of this study is to analyze and determine the effect of Audit Tenure, Company Size, Audit Rotation, and Profitability on Going Concern Audit Opinions in Sub Companies in the Real Estate and Property Sub-Sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research method used in this study is a quantitative research method. The population in this study consists of Property and Real Estate Sub-Sector companies listed on the IDX during the 2021–2024 period, and the sample used in this study is 100 samples. The research results indicate that audit tenure does not affect the going concern audit opinion. Company size has a positive effect on the going concern audit opinion. Audit rotation does not affect the going concern audit opinion. Profitability does not affect the going concern audit opinion. However, audit tenure, company size, audit rotation, and profitability simultaneously have an effect on the going concern audit opinion.